Poly (ε-Caprolactone)/Cellulose Nanofiber Blend Nanocomposites Containing ZrO2 Nanoparticles: A New Biocompatible Wound Dressing Bandage with Antimicrobial Activity - Sina khanmohammadi; Ramin Karimian; Mojtaba Ghanbari Mehrabani; Bahareh Mehramuz; Khudaverdi Ganbarov; Ladan Ejlali; Asghar Tanomand; Fadhil S. Kamounah; Mohammad Ahangarzadeh Rezaee; Mehdi Yousefi; Elham Sheykhsaran; Hossein Samadi Kafil (Tabriz University of Medical Sciences, 2020)
Purpose: In the present study, the poly (ε-caprolactone)/cellulose nanofiber containing ZrO2 nanoparticles (PCL/CNF/ZrO2 ) nanocomposite was synthesized for wound dressing bandage with antimicrobial activity. Methods: PCL/CNF/ZrO2 nanocomposite was synthesized in three different zirconium dioxide amount (0.5, 1, 2%). Also the prepared nanocomposites were characterized by Infrared spectroscopy (FT-IR), X-ray diffraction (XRD), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). In addition, the morphology of the samples was observed by scanning electron microscopy (SEM). Results: Analysis of the XRD spectra showed a preserved structure for PCL semi-crystalline in nanocomposites and an increase in the concentrations of ZrO2 nanoparticles, the structure of nanocomposite was amorphous as well. The results of TGA, DTA, DSC showed thermal stability and strength properties for the nanocomposites which were more thermal stable and thermal integrate compared to PCL. The contact angles of the nanocomposites narrowed as the amount of ZrO2 in the structure increased. The evaluation of biological activities showed that the PCL/CNF/ZrO2 nanocomposite with various concentrations of ZrO2 nanoparticles exhibited moderate to good antimicrobial activity against all tested bacterial and fungal strains. Furthermore, cytocompatibility of the scaffolds was assessed by MTT assay and cell viability studies proved the non-toxic nature of the nanocomposites. Conclusion: The results show that the biodegradability of nanocomposite has advantages that can be used as wound dressing.